Lefort I surgical approach to skull base tumors - Flores Cevallos, Elbio (1989)
We have made a retrospective study of six cases of juvenile nasopharygeal angiofibroma stage III.A and one case of a large osteoma of the ethmoid labyrinth, all of them treated surgically through a bilateral horizontal osteotomy of the maxilla, Lefort I, with very good results. This is a new technique that has been used for the first time in our hospital, facilities the exposure of the skull base and sorrounding structures and allows a complete removal of the tumor with good control of the hemostasis, minimal blood loss and leaving no disfiguring scar on the face. The technique is described in detail (An Fac Med UNMSM II Epoca 1989; a (1-2): 45-48).